Professor Aleksandra Fyodorovna Smyshlyaeva - I. I. Balasheva (Бюллетень сибирской медицины, 2007)
The paper presents biography of Professor Aleksandra Fyodorovna Smyshlyaeva (Tomsk Medical Institute), well-known children's doctor and scientist contributing significantly to development of Russian pediatrics, gifted teacher, and propagandist of medical knowledge.